Influência da sucção mátrica nas condições de fluxo e estabilidade de taludes de uma barragem de terra - Leme, Rosiel Ferreira (2016)
This work has as main objective to evaluate the influence of unsaturation of soils on slope stability during operation in earth dams. For this, a study of slope stability for Pesqueiro Dam was performed to evaluate the safety of the work during the period of operation. Geotechnical parameters used in the analysis were obtained from the testing laboratory on samples taken at the dam and deposit of soil. The conditions of pore pressure in the dam were obtained by transient numerical simulations, simulating the operation of the dam over a period of 6 years. After defining the variation of water pressures during the operation period, the slope stability analysis considering the unsaturation of the soil through the influence of matric suction on the shear strength of the soil were carried out, and through traditional methodologies, which matric suction is not taken into account the shear strength of the material. The results showed that for the downstream slope, stability does not occur significant changes in both the methodologies adopted, due to the internal drainage system, different from the amount of slope, which because of huge changes in water pressures, varies widely stability during the study period. Evaluating the influence of suction in stability, observed difference is an average of 13,8% for the downstream slope and a difference of 29,6% for the upstream slope for both methodologies.